2021
DOI: 10.1016/j.hjdsi.2020.100487
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Lessons from the COVID-19 global health response to inform TB case finding

Abstract: The coronavirus disease 2019 (COVID-19) has emerged as a serious threat to global public health, demanding urgent action and causing unprecedented worldwide change in a short space of time. This disease has devastated economies, infringed on individual freedoms, and taken an unprecedented toll on healthcare systems worldwide. As of 1 April 2020, over a million cases of COVID-19 have been reported in 204 countries and territories, resulting in more than 51,000 deaths. Yet, against the backdrop of the COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…TB patients can experience the stigma against COVID-19, and it must be minimized because it would impact the success of TB treatment. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TB patients can experience the stigma against COVID-19, and it must be minimized because it would impact the success of TB treatment. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…7 Several guidelines to anticipate the impact of the COVID-19 pandemic on TB treatment have been established to mitigate the COVID-19 pandemic, including the sustainability of TB services and information on similarity, differences, and interactions between both diseases. [34][35][36][37] These documents are essential to tackle TB and COVID-19 at the same time. Several major concerns should be considered in controlling TB during the pandemic, such as administrative controls, environmental controls, and respiratory protection.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the COVID-19 response has demonstrated that, with political will, prioritization and investments, it is possible for the international community to mobilize resources, accelerate scientific discovery, and deploy new public health tools to fight a pandemic. 67 These same strategies can thus be employed for TB. However, the COVID-19 response, especially strict lock-downs and mobility restrictions, have also caused immense social and economic suffering and highlighted the need to strike a careful balance between immediate public health gains and unintended health and social side effects.…”
Section: Lessons Learned and Global Health Responsementioning
confidence: 99%
“…At a time of unprecedented political commitment to find, test and treat TB patients, evidence for strategies such as TB screening to inform in-country decision making globally, is vital. Further, the reversal in TB control efforts and case-detection due to the COVID-19 pandemic [47,48] may going forward, make TB screening even more important.…”
Section: Discussionmentioning
confidence: 99%